Originalist Interpretation: A Method of Discovery in Criminal Law (Rechtsvinding in Het Strafrecht) - Setiawan, Peter Jeremiah; Rasyid, Mahendra Harun Ar; Rasyidi, Alfian; Andriawan, Wisnu (Budapest International Research and Critics University, 2021)
Law enforcers are often faced with difficulties when faced with events that meet the formulation in criminal provisions but these are not following the nature (dem wesen nach) of the criminal provisions. To deal with these provisions, one of the legal discovery methods which can be used is to use the interpretation of originalism. The research method in this article is legal research with a statutory approach, conceptual approach, and case approach. Based on the research in this article, it was found that First, the characteristics of the interpretation of originalism as a method of discovery in criminal law is to interpret a statutory regulation according to the original intent of the legislator, so it does not deviate from the original will of the legislator. Second, the use of interpretation of originalism in criminal cases can be seen in the decision number 121/Pid.Sus/2019/PN Mll, which incidentally the judge used the interpretation of originalism related to the true meaning of competence and in the decision number 72/Pid.Sus/2020 /PN Psb, the judge used the interpretation of originalism to interpret the element